Neoliberalism as a Deconstruction of Liberalism in the EU: The Use of Semantic Inversion in the Rule of Law Conditionality Regulation (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
The paper examines tensions between liberalism and neoliberalism in the European Union’s (EU) discourse and response to the Rule of Law crisis. Using qualitative content analysis and network representation, we identify what we define as “semantic inversion”, whereby neoliberal actions are justified with liberal democratic rhetoric. Consequently, by retracing and analyzing the legislative bargaining behind the Rule of Law Conditionality Regulation, we define the trajectory of the conditionality mechanism in the inter-institutional bargaining, identifying several crucial fractures that have reshaped its scope and ambition, showing a significant misalignment between the various actors involved, which seems to be the basis of the observed misalignment in the EU public discourse.
Keywords: Liberalism and Neoliberalism; Semantic Inversion; Rule of Law; European Union